Physicochemical properties and drug-release mechanisms of dual-release bilayer tablet containing mirabegron and fesoterodine fumarate - Lee HG; Park YS; Jeong JH; Kwon YB; Shin DH; Kim JY; Rhee YS; Park ES; Kim DW; Park CW (Drug Design, Development and Therapy, 2019)
Hong-Goo Lee,*,1 Yun-Sang Park,*,1 Jin-Hyuk Jeong,1 Yong-Bin Kwon,1 Dae Hwan Shin,1 Ju-Young Kim,2 Yun-Seok Rhee,3 Eun-Seok Park,4 Dong-Wook Kim,5 Chun-Woong Park11College of Pharmacy, Chungbuk National University, Cheongju 28160, South Korea; 2College of Pharmacy, Woosuk University, Wanju 55338, South Korea; 3College of Pharmacy and Research Institute of Pharmaceutical Sciences, Gyeongsang National University, Jinju 52828, South Korea; 4School of Pharmacy, Sungkyunkwan University, Suwon 16419, South Korea; 5Department of Pharmaceutical Engineering, Cheongju University, Cheongju 28530, South Korea*These authors contributed equally to this workIntroduction: In this study, a dual release bi-layer tablet containing Fesoterodine fumarate (Fst) 5 mg and Mirabegron (Mrb) 50 mg was prepared to investigate the different release behavior of each drug in bilayer tablet. The bilayer tablet was prepared based on monolayer-tablet formulation of each drug.Methods: The optimized bi-layer tablet showed an in vitro dissolution profile similar to commercial reference tablets Toviaz and Betmiga, based on a satisfactory similarity factor. Drug-release kinetics of each drug in the bilayer tablet were evaluated based on dissolution profiles. Drug-release behavior was evaluated by observing the surface of each layer by scanning electron microscopy and measuring the changes in weight and volume of the tablet during dissolution. Drug transfer between each layer was also investigated by Fourier -transform infrared spectroscopic imaging by observing the cross-section of the bilayer tablet cut vertically during dissolution.Results: The release of Fst was well suited for the Higuchi model, and the release of Mrb was well suited for the Hixson-crowell model. Compared with dissolution rate of each monolayer tablet, that of Fst in the bilayer tablet was slightly reduced (5%), but the dissolution rate of Mrb in bilayer tablet was dramatically decreased (20%). Also, a drug-release study confirmed that polymer swelling was dominant in Fst layer compared with polymer erosion, and degradation was dominant in MRB layer. Fourier-transform infrared imaging and 3-D image reconstruction showed that drug transfer in the bilayer tablet correlates with the results of drug-release behavior.Conclusion: These findings are expected to provide scientific insights in the development of a dual-release bilayer drug-delivery system for Fst and Mrb.Keywords: mirabegron, fesoterodine fumarate, swelling property, erosion property, bilayer tablet, FT-IR imaging